Defective cholesterol metabolism in haematopoietic stem cells promotes monocyte-driven atherosclerosis in rheumatoid arthritis. (21st March 2018) - Dragoljevic, Dragana; Kraakman, Michael J; Nagareddy, Prabhakara R; Ngo, Devi; Shihata, Waled; Kammoun, Helene L; Whillas, Alexandra; Lee, Man Kit Sam; Al-Sharea, Annas; Pernes, Gerard; Flynn, Michelle C; Lancaster, Graeme I; et al.
Abstract: Aim: Rheumatoid arthritis (RA) is associated with an approximately two-fold elevated risk of cardiovascular (CV)-related mortality. Patients with RA present with systemic inflammation including raised circulating myeloid cells, but fail to display traditional CV risk-factors, particularly dyslipidaemia. We aimed to explore if increased circulating myeloid cells is associated with impaired atherosclerotic lesion regression or altered progression in RA. Methods and results: Using flow cytometry, we noted prominent monocytosis, neutrophilia, and thrombocytosis in two mouse models of RA. This was due to enhanced proliferation of the haematopoietic stem and progenitor cells (HSPCs) in the bone marrow and the spleen. HSPCs expansion was associated with an increase in the cholesterol content, due to a down-regulation of cholesterol efflux genes, Apoe, Abca1, and Abcg1 . The HSPCs also had enhanced expression of key myeloid promoting growth factor receptors. Systemic inflammation was found to cause defective cellular cholesterol metabolism. Increased myeloid cells in mice with RA were associated with a significant impairment in lesion regression, even though cholesterol levels were equivalent to non-arthritic mice. Lesions from arthritic mice exhibited a less stable phenotype as demonstrated by increased immune cell infiltration, lipid accumulation, and decreased collagen formation. In a progression model, we noted monocytosis, enhanced monocytes recruitment to lesions, and increased plaque macrophages. This was reversed with administration of reconstituted high-density lipoprotein (rHDL). Furthermore, RA patients have expanded CD16 + monocyte subsets and a down-regulation of ABCA1 and ABCG1. Conclusion: Rheumatoid arthritis impairs atherosclerotic regression and alters progression, which is associated with an expansion of myeloid cells and disturbed cellular cholesterol handling, independent of plasma cholesterol levels. Infusion of rHDL prevented enhanced myelopoiesis and monocyte entry into lesions. Targeting cellular cholesterol defects in people with RA, even if plasma cholesterol is within the normal range, may limit vascular disease.